2013
DOI: 10.11648/j.sjph.20130101.16
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Network and Binary Logistic Regression in Detection of Diabetes Status

Abstract: Abstract:Various methods can be applied to build predictive models for the clinical data with binary outcome variables.This research aims to compare and explore the process of constructing common predictive models. Models based on an artificial neural network (the multilayer perceptron) and binary logistic regression were applied and compared in their ability to classifying disease-free subjects and those with diabetes mellitus(DM) diagnosed by glucose level. Demographic, enthropometric and clinical data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…13 Another study found that ANN performed better than binary logistic regression models in the detection of diabetes status from clinical data. 14 A study related to the prediction of heart disease using ANNs with a clinical data set of 13 variables is similar to this study, and they found higher accuracy, sensitivity, and specificity than a state vector machine comparison. 15 These and other studies show the usefulness of ANNs for pattern detection in real-world clinical data sets.…”
Section: Introductionsupporting
confidence: 70%
“…13 Another study found that ANN performed better than binary logistic regression models in the detection of diabetes status from clinical data. 14 A study related to the prediction of heart disease using ANNs with a clinical data set of 13 variables is similar to this study, and they found higher accuracy, sensitivity, and specificity than a state vector machine comparison. 15 These and other studies show the usefulness of ANNs for pattern detection in real-world clinical data sets.…”
Section: Introductionsupporting
confidence: 70%
“…It should be noted that due to the simplicity of interpretation of the variables in the logistic regression model, applying it clinically is more comprehensible. Rahman et al compared the accuracy of ANN and binary logistic regression models for predicting glucose status (21). They showed a significantly better performance of ANN for detection of impaired glucose tolerance and T2DM patients from disease-free ones (21).…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al compared the accuracy of ANN and binary logistic regression models for predicting glucose status (21). They showed a significantly better performance of ANN for detection of impaired glucose tolerance and T2DM patients from disease-free ones (21). Omurlu et al compared performance of logistic regression and ANN for prediction of albuminuria in T2DM and demonstrated that multilayer perceptron had the highest predictive capability for the presence of albuminuria (22).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, rapid developments in artificial intelligence techniques have led to the adoption of machine learning methods to construct diagnostic and predictive models of various diseases. Intelligent diagnosis and prediction methods for different diseases can be classified into two categories: one based on traditional single learner and the other based on multiple learners, such as the diabetes diagnosis method based on a single learner proposed by Rahman et al [ 22 ] and the congestive heart failure diagnosis method based on multiple learners proposed by Isler et al [ 23 ]. In the diagnosis and prediction of diabetes mellitus, the approach based on a single learner can provide satisfactory results with higher efficiency.…”
Section: Introductionmentioning
confidence: 99%